Two rare cases of maxillary pneumocoele. Issue 6 (July 2019) - Zhao, C.; Zhao, Y.; Yang, J.; Wang, Z.
Abstract: Pathological expansion of the paranasal sinus by air is rare, and may cause severe deformation of the overlying bone and tissue. We present two cases of young adults with maxillary pneumocoeles that were diagnosed by computed tomography, and discuss the differential aetiology.